EXTRACTION, PURIFICATION, AND USE OF TOMATO BIOACTIVES: A CRITICAL REVIEW FROM CHEMICAL AND INDUSTRIAL VIEWPOINTS. - Arfi, Febrina (Barkah Publishing, 2025)
Tomatoes (Solanum lycopersicum L.) are a valuable source of phytochemicals, particularly lycopene, β-carotene, flavonoids, and phenolic acids. These compounds are known for their properties that combat oxidation, reduce inflammation, and prevent diseases. This review synthesizes current methods for extracting and purifying bioactive compounds from tomatoes, while also looking at their applications in the food, nutraceutical, and cosmetic industries. Although traditional solvent-based extraction is still the most common due to its high efficiency, greener methods like supercritical CO₂ extraction and enzyme-assisted extraction are becoming more important for sustainable practices. Chromatographic purification offers better selectivity compared to techniques like filtration or centrifugation, but cost and scalability remain barriers to wider use. The applications of lycopene and other tomato phytochemicals range from dietary supplements and functional foods to anti-aging products. Overall, this synthesis highlights the need to advance green extraction methods, along with effective purification strategies, to fully utilize tomatoes as a rich source of bioactive compounds across various industries